Global economy, global justice : theoretical objections and policy alternatives to neoliberalism - DeMartino, George (Contemporary political economy series., 2000)
"Global Economy, Global Justice explores a vital question that is suppressed in most economics texts: "what makes for a good economic outcome?" Neoclassical theory embraces the normative perspective of "welfarism" to assess economic outcomes. This volume demonstrates the flaws of this perspective - flaws that stem from objectionable assumptions about human nature, society and science. Exposing these failures, the book obliterates the ethical foundations of global neoliberalism. George DeMartino probes heterodox economic traditions and philosophy in search of an ethically viable alternative to welfarism. Drawing on the work of Amartya Sen, DeMartino proposes the egalitarian principle of the "global harmonization of capabilities" to guide economics. This principle provides a basis for resisting oppression the world over while nevertheless demanding respect for cultural diversity. DeMartino puts this principle to work adjudicating contemporary debates over global policy regimes, and completes the book with a set of egalitarian global policies for the year 2025. Global Economy, Global Justice will appeal to those seeking to understand the intersection between economics and political philosophy."--Jacket